2013
DOI: 10.3347/kjp.2013.51.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Toxoplasma gondii Acute Infection on Cholinesterase Activities of Wistar Rats

Abstract: Several studies have shown the mechanisms and importance of immune responses against Toxoplasma gondii infection and the notable role of cholinesterases in inflammatory reactions. However, the association between those factors has not yet been investigated. Therefore, the aim of this study was to evaluate the acetylcholinesterase (AChE) activity in blood and lymphocytes and the activity of butyrylcholinesterase (BChE) in serum of rats experimentally infected with T. gondii during the acute phase of infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Considering the lymphocyte cell types that are predominant in gerbils (45), the reason of the high percentage of neutrophil is probably an inflammatory response to the tachyzoite proliferation during infection. However, Tonin et al (47) reported that the numbers of circulating lymphocytes were increased in T. gondiiinfected rats. Tonin et al (47) found that the number of lymphocytes was higher in toxoplasma-infected rats however in this study neutrophil percentage was found to be higher in toxoplasma-infected gerbils.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering the lymphocyte cell types that are predominant in gerbils (45), the reason of the high percentage of neutrophil is probably an inflammatory response to the tachyzoite proliferation during infection. However, Tonin et al (47) reported that the numbers of circulating lymphocytes were increased in T. gondiiinfected rats. Tonin et al (47) found that the number of lymphocytes was higher in toxoplasma-infected rats however in this study neutrophil percentage was found to be higher in toxoplasma-infected gerbils.…”
Section: Discussionmentioning
confidence: 98%
“…However, Tonin et al (47) reported that the numbers of circulating lymphocytes were increased in T. gondiiinfected rats. Tonin et al (47) found that the number of lymphocytes was higher in toxoplasma-infected rats however in this study neutrophil percentage was found to be higher in toxoplasma-infected gerbils. This discrepancy can be related to the different sampling period of these studies.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas, indirect effects can involve immune response to chronic toxoplasmosis (28); the direct effects are probably due to the mechanical presence of the T. gondii in the brain or their effects or products on neuronal cells biology (29). Regarding direct effects of chronic toxoplasmosis, infection by T. gondii is able to affect cholinesterase activity and enhance the AChE levels in brain of infected mice (14, 15). ACh play a main role in the regulation of learning and memory functions (13).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, T. gondii infection enhances the activity of acetylcholinesterase (AChE) as a membrane-bound enzyme which hydrolyses ACh (14, 15). Donepezil hydrochloride is a well-known anti-dementia drug that increases acetylcholine levels via inhibition of AChE and improve learning and memory impairments (16).…”
Section: Introductionmentioning
confidence: 99%
“…Cholinesterases are enzymes present in cholinergic and noncholinergic tissues, as well as in blood and other body fluids. The AChE is a mernbrane-bound enzyme mainly found in the brain, muscles, erythrocytes, Iymphocytes, and cholinergic neurons [19,20] , while BChE is present in the intestine, liver, kidney, heart, lung, brain, and serum [21,22] . AChE inhibits activation of macrophages and release of proinflammatory cytokines, such as IL-6, TNF-α, IL-1, and IL-18 [23] .…”
Section: Group Of Animalsmentioning
confidence: 99%